A common haplotype of the TNF receptor 2 gene modulates endotoxin tolerance. - Fairfax, B; Davenport, E; Makino, S; Hill, A; Vannberg, F; Knight, J (2011)
Endotoxin tolerance is characterized by the suppression of further TNF release upon recurrent exposure to LPS. This phenomenon is proposed to act as a homeostatic mechanism preventing uncontrolled cytokine release such as that observed in bacterial sepsis. The regulatory mechanisms and interindividual variation of endotoxin tolerance induction in man remain poorly characterized. In this paper, we describe a genetic association study of variation in endotoxin tolerance among healthy individuals. We identify a common promoter haplotype in TNFRSF1B (encoding TNFR2) to be strongly associated with reduced tolerance to LPS (p = 5.82 × 10(-6)). This identified haplotype is associated with increased expression of TNFR2 (p = 4.9 × 10(-5)), and we find basal expression of TNFR2, irrespective of genotype and unlike TNFR1, is associated with secondary TNF release (p < 0.0001). Functional studies demonstrate a positive-feedback loop via TNFR2 of LPS-induced TNF release, confirming this previously unrecognized role for TNFR2 in the modulation of LPS response.